Ups and downs of infections with the broad fish tapeworm Dibothriocephalus latus in Europe from 1900 to 2020: Part I - Králová-Hromadová, Ivica; Radačovská, Alžbeta; Čisovská Bazsalovicsová, Eva; Kuchta, Roman (Advances in parasitology, 2021)
The broad fish tapeworm, Dibothriocephalus latus (Diphyllobothriidea), is the most frequent causative agent of diphyllobothriosis, a fish-borne zoonosis, in Europe. Diphyllobothriosis is characterized by the transmission of D. latus larvae to humans via the consumption of raw, marinated, smoked or inadequately cooked fish products. The most important European foci of diphyllobothriosis have been Fennoscandia, the Baltic region, the Alpine lakes region, the Danube River region, and several endemic regions in Russia. This review provides basic data on the biology, life cycle, host specificity, methods of identification of D. latus, and a detailed summary of its occurrence in intermediate and definitive hosts in Fennoscandia and the Baltic, Alpine, and Danube regions during the last 120 years (1900-2020). Deeper insight into the unique pattern of distribution of D. latus in endemic regions is provided. The numbers of records are associated with several milestones of particular time periods. The first milestone (historical), which influenced studies on D. latus in Europe, was the period during and after World War II (1941-1950). The second milestone (epidemiological) was the decade 1981-1990, when previous massive health campaigns led to a marked decline of diphyllobothriosis in Europe and less published data on D. latus. Based on recent data, the broad fish tapeworm is either absent or present at very low prevalences in Fennoscandia and the Baltic and Danube regions, but the Alpine lakes region represents a continuous ongoing circulation of the parasite in the natural environment and humans.
Keywords: Diphyllobothriasis; Humans; Diphyllobothrium; Human parasites; lidé; zoonózy; zvířata; Europe; Fish-borne zoonosis; Diphyllobothriosis; Fish tapeworms; Zoonoses; Geographic distribution; difylobotriáza; Animals; Diphyllobothriidea; Food-borne diseases; Evropa; Cestoda